Karak Non Boraks - Tri Astuti; Muryoto Muryoto; Tuntas Bagyono (Poltekkes Kemenkes Yogyakarta, 2018)
In the making of karak, people still use bleng (borax), eventhough according to regulation issu-ed by the MoH of Indonesia No. 722/Menkes/ Per/IX/88, borax is declared as a hazardous sub-stance and so that is prohibited to be used in food processing because its toxicity to all cells can adversely affect human health. This study produces non-borax karak by utilizing cassava starch as borax substitute. The purpose of this study was to measure the organoleptic charac-teristics of formulations I, II, III, IV, V and VI (control), as well as to determine the best formu-lation, i.e. has same organoleptic tests scores as the control has, by conducting a post-test with control group designed experiment in four times replication The data were analyzed using one way anava test and followed by LSD test both at ?=0,05. The results showed that the organo-leptic score of formulation I was 3,23; formulation II was 2,81; formulation III was 2,73; formula-tion IV was 3,11; formulation V was 3,27; and the control was 3,23. Therefore, it can be conclu-ded that the best formulation is formulation I, which is composed of 20 % cassava starch and 80 % rice.